Prevalence and determinants of hypertension among business class community of Lahore, Pakistan (International Current Pharmaceutical Journal, 2016)
Hypertension is one of the leading health issue in developing countries. There are many factors associated with hypertension like obesity, excessive intake of salt, smoking and drinking alcohol. Current study aims to assess the prevalence and determinants of hypertension among business class community in Lahore. A community based survey in Lahore was conducted to evaluate the prevalence and determinants in business class community aged 20- 45 year. Questionnaire was designed, translated into local language and 400 participants were interviewed as per structured questionnaire, collected data was analyzed using statistical software SPSS 22. The prevalence of hypertension among study population was 37.5%. Results were astonishing only 32% of hypertensive patients were taking antihypertensive pills. Being overweight was strongly associated with hypertension, also excessive salt intake and sedentary life style were the contributing factors. There is dire need of awareness to be related hypertension among business class community counselling them about salt intake, smoking and regular exercise.Farooq et al., International Current Pharmaceutical Journal, September 2016, 5(10): 79-81http://www.icpjonline.com/documents/Vol5Issue10/01.pdf